Frozen II [videorecording (DVD)] - Buck, Chris; Lee, Jennifer, (Screenwriter) (Walt Disney Studios Home Entertainment, 2020)
Anna, Elsa, Kristoff, Olaf, and Sven leave Arendelle to travel to an ancient, autumn-bound forest of an enchanted land. They set out to find the origin of Elsa's powers in order to save their kingdom.